PENGARUH LUAS LAHAN PANEN PADI DAN DAK FISIK PERTANIAN TERHADAP PRODUKSI PADI DI JAWA TIMUR - Faisol Muttaqin, Alfin; Suman, Agus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
East Java is the largest rice producer of all provinces in Indonesia, according to BPS, East Java is able to produce 9.90 million Gabah Kering Giling (GKG), while rice is the staple food source of the majority of Indonesian people. There are several problems related to the agricultural sector in East Java, the most serious problem is the conversion of agricultural land which threatens national food security, It was recorded that in 2019 East Java experienced agricultural land conversion of 9,597 hectares., this has an impact on the decline in rice production in East Java in the span of 2020 to 2022. The allocation of central government funds to the agricultural sector in each region has also decreased due to the Covid-19 pandemic. This study aims to determine the effect of changes in fertilizer subsidy policies, rice harvest area, and Dana Alokasi Khusus (DAK) for Agriculture on rice production in 38 districts/cities in East Java calculated using the panel data regression method.